1999
DOI: 10.1099/0022-1317-80-7-1725
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide sequences and further characterization of human papillomavirus DNA present in the CaSki, SiHa and HeLa cervical carcinoma cell lines.

Abstract: The complete nucleotide sequences of the human papillomavirus type 16 (HPV-16) variants present in the CaSki and SiHa cervical carcinoma cell lines and the primary subgenomic HPV-18 variant present in the HeLa cervical carcinoma cell line were determined using overlapping bulk PCR products as templates. PCR-based methods were also used to characterize five previously unreported CaSki HPV-16 genomic disruptions and the 5h cellular-viral junction common to all HeLa HPV-18 subgenomic structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
153
0
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(168 citation statements)
references
References 52 publications
13
153
0
2
Order By: Relevance
“…1 ± 3,38 ± 40 HPV 16 and 18 genotypes account for greater than 65% of all HPV DNA-positive invasive cervical carcinomas in multi-institutional studies 1,41 and are found in the majority of human cervical carcinoma-derived cell lines. 42 In this context, the intervention of HPV infection in the carcinogenesis is mainly supported by E6 and E7 oncoproteins which abrogate p53 and pRb functions; the genes of those two factors retain usually a wild-type form. 43 The recent demonstration, that p53 and pRb disruptions are 44 In order to explore new drugs to treat uterine cervix cancer, we decided to study the responses of three different human cervical carcinoma cell lines under staurosporine exposure.…”
Section: Discussionmentioning
confidence: 99%
“…1 ± 3,38 ± 40 HPV 16 and 18 genotypes account for greater than 65% of all HPV DNA-positive invasive cervical carcinomas in multi-institutional studies 1,41 and are found in the majority of human cervical carcinoma-derived cell lines. 42 In this context, the intervention of HPV infection in the carcinogenesis is mainly supported by E6 and E7 oncoproteins which abrogate p53 and pRb functions; the genes of those two factors retain usually a wild-type form. 43 The recent demonstration, that p53 and pRb disruptions are 44 In order to explore new drugs to treat uterine cervix cancer, we decided to study the responses of three different human cervical carcinoma cell lines under staurosporine exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Cervical cancer cell lines CaSki, SiHa (HPV-16-positive), HeLa (HPV-18-positive) and C-33A (HPV-negative) and their growth conditions have been described (Meissner, 1999). Three clonal populations of the HPV-16 cervical cell line W12, 20863 (episomal HPV-16), 20861 and 201402 (integrated HPV-16) were obtained from the laboratories of Dr Margaret Stanley and Dr Paul Lambert (Medical Research Council, UK and University of Wisconsin, WA, USA, respectively).…”
Section: Cell Linesmentioning
confidence: 99%
“…Studies of control and eps8 small interfering RNA (siRNA) -expressing cells derived from HeLa (HPV18 DNA-positive; ref. 30) and SiHa (HPV16 DNA-positive; ref. 30) cervical caner cells indicated that Eps8 played a critical role in cell proliferation in culture and tumor formation in mice.…”
Section: Introductionmentioning
confidence: 99%
“…30) and SiHa (HPV16 DNA-positive; ref. 30) cervical caner cells indicated that Eps8 played a critical role in cell proliferation in culture and tumor formation in mice. By virtue of (a) down-regulation of cyclins D1, D3, and E, (b) elevation of p53 and p21 Waf1/Cip1 , and (c) decrease of hyperphosphorylated Rb, diminished Eps8 could effectively arrest cell cycle at G 1 phase.…”
Section: Introductionmentioning
confidence: 99%